Play interventions to reduce anxiety and negative emotions in hospitalized children. Issue 1 (December 2016) - Li, William; Chung, Joyce; Ho, Ka; Kwok, Blondi
Abstract Background Hospitalization is a stressful and threatening experience, which can be emotionally devastating to children. Hospital play interventions have been widely used to prepare children for invasive medical procedures and hospitalization. Nevertheless, there is an imperative need for rigorous empirical scrutiny of the effectiveness of hospital play interventions, in particular, using play activities to ease the psychological burden of hospitalized children. This study tested the effectiveness of play interventions to reduce anxiety and negative emotions in hospitalized children. Methods A non-equivalent control group pre-test and post-test, between subjects design was conducted in the two largest acute-care public hospitals in Hong Kong. A total of 304 Chinese children (ages 3-12) admitted for treatments in these two hospitals were invited to participate in the study. Of the 304 paediatric patients, 154 received hospital play interventions and 150 received usual care. Results Children who received the hospital play interventions exhibited fewer negative emotions and experienced lower levels of anxiety than those children who received usual care. Conclusion This study addressed a gap in the literature by providing empirical evidence to support the effectiveness of play interventions in reducing anxiety and negative emotions in hospitalized children. Findings from this study emphasize the significance of incorporating hospital play interventions to provide holistic and quality care to ease the psychological burden of hospitalized children. Trial registration ClinicalTrials.govNCT02665403 . Registered 22 January 2016.